2022
DOI: 10.1002/pmic.202100143
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analyses reveal the dynamics of protein and amino acid accumulation during soybean seed development

Abstract: Using high throughput tandem mass tag (TMT) based tagging technique, we identified 4172 proteins in three developmental stages: early, mid, and late seed filling. We mapped the identified proteins to metabolic pathways associated with seed filling. The elevated abundance of several kinases was observed from the early to mid-stages of seed filling, indicating that protein phosphorylation was a significant event during this period. The early to late seed filling stages were characterized by an increased abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Mass spectrometry-based proteomics combined with advanced bioinformatics is a powerful platform not only to determine the seed proteome profile from many legumes but also to identify, quantify, and demonstrate the conformational changes of many allergenic proteins. Despite being a crop high in nutrients, research has shown that mung beans are also cross-reactive with IgE. ,, Previous findings verified both naso-bronchial sensitization and the allergic reaction to mung bean consumption in clinical samples. ,, To date, only a handful of research papers have been published on the mung bean proteome. , However, to the best of our knowledge, no comparative analysis of the mung bean cultivar-specific seed proteome has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry-based proteomics combined with advanced bioinformatics is a powerful platform not only to determine the seed proteome profile from many legumes but also to identify, quantify, and demonstrate the conformational changes of many allergenic proteins. Despite being a crop high in nutrients, research has shown that mung beans are also cross-reactive with IgE. ,, Previous findings verified both naso-bronchial sensitization and the allergic reaction to mung bean consumption in clinical samples. ,, To date, only a handful of research papers have been published on the mung bean proteome. , However, to the best of our knowledge, no comparative analysis of the mung bean cultivar-specific seed proteome has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the level of expression of GmCGS2 and contents of free Met and other free amino acids was also mainly reflected at the same stages of the transgenic seeds, leading to an increase in the contents of total amino acids and soluble protein in transgenic mature seeds ( Figure S2C , Figure 2 and Figure 3 ). Studies have shown that most sulfur metabolic enzymes are highly abundant at the early stages of seed development compared with the mid- and late stages, and this was accompanied by an increased synthesis of sulfur-containing amino acids [ 52 , 53 , 54 ]. In addition, many studies suggested a positive correlation between the level of expression of AtCGS and accumulation of free Met and other free amino acids [ 3 , 4 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the synthesis of storage protein begins at the early stages of developing seeds, which is consistent with the rapidly decreasing content of free amino acids after this stage [ 55 , 56 ]. Therefore, we considered that GmCGS2 mainly functions in developing seeds at early stages, and the moderate increase in the transcript level of GmCGS2 and content of free Met in the late developmental stages was likely due to the additional needs of storage protein synthesis ( Figure S2C and Figure 2 ) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…S8C and D). At the transcriptional level, the induction of the expression of the genes controlling the biosynthesis of cupins, seed storage proteins, and oleosins, proteins involved in the production of oil bodies, and genes encoding albumin [35][36][37] start as soon as the cotyledon stage of the seed (Fig. S8B, clusters #10 to 13, red square).…”
Section: Cell Type Annotation Of the Tabula Glycine Clustersmentioning
confidence: 99%